2023
DOI: 10.7717/peerj.15344
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bamlanivimab alone or in combination with etesevimab on subsequent hospitalization and mortality in outpatients with COVID-19: a systematic review and meta-analysis

Abstract: Background Coronavirus disease 2019 (COVID-19) has caused an enormous loss of life worldwide. The spike protein of the severe acute respiratory syndrome coronavirus 2 is the cause of its virulence. Bamlanivimab, a recombinant monoclonal antibody, has been used alone or in combination with etesevimab to provide passive immunity and improve clinical outcomes. A systematic review and meta-analysis was conducted to investigate the therapeutic effects of bamlanivimab with or without etesevimab (BAM/ETE) treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…Further, the administration of bamlanivimab lowered nasopharyngeal viral levels and faster reductions in inflammatory markers and viral decay in hospitalized COVID-19 patients whereas it did not reduce the symptom duration in nonhospitalized adults with early variants of SARS-CoV-2 [151]. Blocking viral attachment and cell entry with SARS-CoV-2 neutralizing antibodies (BLAZE-1) clinical trial showed that bamlanivimab monotherapy and combination therapy bamlanivimab with etesevimab were efficacious in reducing the risk of COVID-19related hospitalization and progression to severe disease [152,153]. Though the FDA revoked the EUA due to poor efficacy, it is still available as a combination therapy [150].…”
Section: Repurposing Of Monoclonal Antibodiesmentioning
confidence: 99%
“…Further, the administration of bamlanivimab lowered nasopharyngeal viral levels and faster reductions in inflammatory markers and viral decay in hospitalized COVID-19 patients whereas it did not reduce the symptom duration in nonhospitalized adults with early variants of SARS-CoV-2 [151]. Blocking viral attachment and cell entry with SARS-CoV-2 neutralizing antibodies (BLAZE-1) clinical trial showed that bamlanivimab monotherapy and combination therapy bamlanivimab with etesevimab were efficacious in reducing the risk of COVID-19related hospitalization and progression to severe disease [152,153]. Though the FDA revoked the EUA due to poor efficacy, it is still available as a combination therapy [150].…”
Section: Repurposing Of Monoclonal Antibodiesmentioning
confidence: 99%